Differential response of clones of eucalypt to glyphosate - Carvalho, Leonardo Bianco de; Costa Aguiar Alves, Pedro Luis da [UNESP]; Costa, Flvia Regina da (Univ Federal Vicosa, 2015)
Weed control is commonly performed by the inter-row mechanical weeding associated to intrarow glyphosate directed spraying, causing a risk for drift or accidental herbicide application, that can affect the crop of interest. The objective was to evaluate the response of clones C219, GG100, I144, and I224 of eucalypt (Eucalyptus grandis x E. urophylla) to glyphosate doses of 0, 18, 36, 72, 180, 360, and 720 g of acid equivalent per hectare. The clones showed different growth patterns with regard to height, leaf number, stem dry weight, relative growth rate, net assimilation rate, and relative leaf growth rate. The clones I144 and GG100 were more susceptible to glyphosate, showing the doses required to reduce dry weight by 50% of 113.4 and 119.6 g acid equivalent per hectare, respectively. The clones C219 and I224 were less susceptible to glyphosate, showing the doses required to reduce dry weight by 50% of 237.5 and 313.5 g acid equivalent per hectare, respectively. Eucalyptus clones respond differently to glyphosate exposure, so that among I224, C219, GG100, and I144, the susceptibility to the herbicide is increasing.

O controle de plantas daninhas é comumente feito com roçadas na entrelinha associada a aplicações dirigidas de glyphosate na linha de plantio de culturas arbóreas, acarretando risco de deriva ou aplicação acidental do herbicida, que pode afetar a cultura de interesse. O objetivo foi avaliar a resposta dos clones C219, GG100, I144 e I224 de eucalipto (Eucalyptus grandis x E. urophylla) a doses de glyphosate de 0, 18, 36, 72, 180, 360 e 720 g de equivalente ácido por hectare. Os clones apresentaram padrões de crescimento distintos no que se refere a altura da planta, número de folhas, massa seca do caule, taxa de crescimento relativo, taxa de assimilação líquida e taxa de crescimento foliar relativo. Os clones I144 e GG100 foram mais suscetíveis ao glyphosate, sendo as doses necessárias para reduzir a massa seca em 50% de 113,4 e 119,6 g ea ha-1, respectivamente. Os clones C219 e I224 foram menos suscetíveis ao glyphosate, sendo as doses necessárias para reduzir a massa seca em 50% de 237,5 e 313,5 gae ha-1, respectivamente. Clones de eucalipto respondem diferentemente à exposição ao glyphosate, e entre I224, C219, GG100 e I144 a suscetibilidade é aumentada.
Resposta diferencial de clones de eucalipto a glyphosate
Keywords: Eucalyptus; N-(phosphonomethyl)-glycine; Spray drift